Operations Management at Sihaf - A Syrian Restaurant in Malaysia - Abo Hsini, Mohammed (IIUM Journal of Case Studies in Management, 2019)
This case aims to discuss the operations strategies of the Sihaf Restaurant. The restaurant is small and serves traditional Syrian cuisine. First part of the case consists of the history and background of Sihaf. This is followed by description of the restaurant’s vision, mission, logo, SWOT analysis, product life cycle, and competitive strategies. Second part of the case study analyzes the most important strategies pertaining to location, layout, and quality management which had been practiced by the owner of Sihaf. Moreover, this case includes factors of selecting those operations strategies, measures the level of their efficiency, and what are the advantages and disadvantages of each strategy. Third part contains an evaluation which was conducted to determine the efficiency of Sihaf.